Personnel Policies at the Union Bank of Australia: Evidence from the 1888–1900 Entry Cohorts - Seltzer, Andrew; Merrett, David (Journal of Labor Economics, 2000)
This article uses personnel, payroll, and other records from the Union Bank of Australia to examine internal labor markets. It is shown that employment was characterized by limited ports of entry, impersonal rules for pay and promotion, well‐defined career ladders, shielding from the external labor market, and a long‐term employment relationship. In addition tenure within the bank was rewarded considerably more than experience elsewhere, and compensation increased considerably after 25–30 years tenure. These facts are partially consistent with the human capital, matching, and contract theory models but cannot be fully explained by any one model.